2020
DOI: 10.3390/antiox9101006
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Polyphenols against Glyco-Oxidative Stress: Involvement of Glyoxalase Pathway

Abstract: Chronic high glucose (HG) exposure increases methylglyoxal (MGO)-derived advanced glycation end-products (AGEs) and is involved in the onset of pathological conditions, such as diabetes, atherosclerosis and chronic-degenerative diseases. Under physiologic conditions the harmful effects of MGO are contrasted by glyoxalase system that is implicated in the detoxification of Reactive Carbonyl Species (RCS) and maintain the homeostasis of the redox environment of the cell. Polyphenols are the most abundant antioxid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(81 reference statements)
2
15
1
Order By: Relevance
“…There are studies that reported the GLO I activity to be high in skeletal muscle ( 27) but low in liver (28) in DOI: 10.37990/medr.983276 diabetic rats. GLO II activity was similarly discovered to be normal in the tissues of small intestine (29) and high in skeletal muscle (30) but low in kidney (31) and liver (32). Both GLO I and GLO II activities were found to be reduced in the liver tissue of diabetic rats in this study, which is consistent with some of the current literature.…”
Section: Resultssupporting
confidence: 91%
“…There are studies that reported the GLO I activity to be high in skeletal muscle ( 27) but low in liver (28) in DOI: 10.37990/medr.983276 diabetic rats. GLO II activity was similarly discovered to be normal in the tissues of small intestine (29) and high in skeletal muscle (30) but low in kidney (31) and liver (32). Both GLO I and GLO II activities were found to be reduced in the liver tissue of diabetic rats in this study, which is consistent with some of the current literature.…”
Section: Resultssupporting
confidence: 91%
“…Overall, these results are in agreement with our previous studies that described an in vitro role of POE against glucose-induced glycation of human serum albumin [ 5 ]. Moreover, other studies have demonstrated the ability of polyphenols to exert a protective effect against oxidative stress and formation of AGEs in Caco-2 cells [ 14 ]. In addition, previous studies have reported that some phenolic compounds exert a protective effect against oxidative stress, either by reducing ROS production during the glycation process or by trapping of dicarbonyl species [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A first UPLC characterization analysis showed that POE consists of 88% phenolic compounds, mostly represented by D-(+)-catechin, and less by gallic acid, ferulic acid, (−)-epicatechin, and chlorogenic acid [8] (Figure 1). Among the biological properties of dietary polyphenols, growing attention has been devoted to their ability to modulate post-prandial increases in glucose levels and to modulate intestinal integrity and oxidative damage [9][10][11][12][13][14]. In fact, high post-prandial plasma glucose concentrations are associated with an increased risk of developing type 2 diabetes (T2D) and metabolic syndrome [15].…”
Section: Of 14mentioning
confidence: 99%
“…Thus, a moderate MGO level increase under OxeS conditions could account to the coordination of cell metabolism with gene expression. It has been recently proposed that S-glutathionylation and MGO-mediated glycation, which can both modulate the activity and stability of proteins involved in cellular homeostasis and adaptive stress responses, may act simultaneously and synergistically [ 45 , 62 ]. Both mechanisms have been shown to occur in cellular models and surgical samples of cerebral cavernous malformations, being affected by KRIT1 loss-of-function and influenced by the impairment of cellular redox homeostasis ([ 45 , 63 ] and refs therein), confirming their connection.…”
Section: S-glutathionylation and Oxidative Stressmentioning
confidence: 99%